2020
DOI: 10.34190/ejise.20.23.1.005
|View full text |Cite
|
Sign up to set email alerts
|

O2O Adoption Benefits: A Managerial Perspective of Customer Benefits

Abstract: Online‑to‑offline (O2O) is a fast‑growing business innovation, pointing online customers to physical locations where they can more closely inspect – and purchase – their desired products, or can collect them after ordering online. However, the growth of O2O may be limited by the lack of reliable understanding of its benefits to customers. This study aims to remedy this lack of knowledge, by analyzing the transcripts of 24 semi‑structured interviews with managers. The study finds that O2O benefits customers in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…In this way, sufficient information exchange can be realized, and resources can be optimally exploited due to the development of mobile phone-based communication technology. The development of O2O e-commerce is unprecedentedly prosperous worldwide, especially in Asia, and in various industries such as dining, transportation, tourism, and sharing space [35]. More recently, the O2O food delivery industry has emerged as the third-party platform connecting individual customers and native restaurants to arrange online orders and deliveries [36].…”
Section: O2o Business and Ofdsmentioning
confidence: 99%
“…In this way, sufficient information exchange can be realized, and resources can be optimally exploited due to the development of mobile phone-based communication technology. The development of O2O e-commerce is unprecedentedly prosperous worldwide, especially in Asia, and in various industries such as dining, transportation, tourism, and sharing space [35]. More recently, the O2O food delivery industry has emerged as the third-party platform connecting individual customers and native restaurants to arrange online orders and deliveries [36].…”
Section: O2o Business and Ofdsmentioning
confidence: 99%
“…Top management support, trial ability, competence of cloud vendors, resistance to new technology, compatibility and existence of IT infrastructure are realized as key factors influencing cloud computing adoption. Ray (2016) and Ogunlolu & Rajanen (2019) proposed unifying model of cloud adoption by organizations. Ogunlolu & Rajanen (2019) cover a systematic literature review was employed to investigate the adoption factors studied in previous empirical settings.…”
Section: Developing Economiesmentioning
confidence: 99%
“…For example, system availability and reliability, cost effectiveness, privacy and security, top management support, and market pressure are among the factors influencing adoption. Ray (2016) categorized environmental, organizational, technological, and financial. Bakasa & Pekane (2021), further revealed that security, cloud service provider adoption framework, data sovereignty, data latency, data center location and the disaster recovery strategy are considered for selecting a preferred CC service provider.…”
Section: Developing Economiesmentioning
confidence: 99%